2013
DOI: 10.1007/s11999-013-2899-5
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid Could Be Used for Antibiotic-loaded Bone Cement for Musculoskeletal Tuberculosis: An In Vitro Study

Abstract: Background Antibiotic-loaded bone cement (ALBC) has been used in serious cases of musculoskeletal tuberculosis, but the type and amount of antibiotic that should be used in ALBC have not been determined. Questions/purposes We therefore determined the (1) elution characteristics and (2) antimycobacterial activity of isoniazid-and rifampicin-loaded bone cement. Methods A total of 240 elution samples of each of three discs from 40 g bone cement mixed with one of eight dosages: 1 g, 2 g, and 4 g isoniazid, 1 g, 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
3
19
0
1
Order By: Relevance
“…From this, it can be determined that the specific antibiotic can affect the specific release profile, which influences the antibiotic of choice for clinicians. Just as Anguita-Alonso et al and others demonstrated [2,16,27], we noticed that adding the rifamycins slowed the curing of the PMMA beads. This may potentially limit the use of rifamycin-impregnated PMMA beads prepared at the time of surgery in the operating room as a result of the time constraint.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…From this, it can be determined that the specific antibiotic can affect the specific release profile, which influences the antibiotic of choice for clinicians. Just as Anguita-Alonso et al and others demonstrated [2,16,27], we noticed that adding the rifamycins slowed the curing of the PMMA beads. This may potentially limit the use of rifamycin-impregnated PMMA beads prepared at the time of surgery in the operating room as a result of the time constraint.…”
Section: Discussionsupporting
confidence: 66%
“…Although rifampin has been documented to have activity against staphylococcal biofilms in vitro and has been indicated for use as an oral or intravenous combination therapy for the treatment of staphylococcal osteoarticular infections [12,21], few studies have evaluated the potential use of rifampin or rifamycin derivatives addressing local delivery of antimicrobials for treatment of contaminated open fractures [28,29,38]. We demonstrate that rifampin and rifamycin derivatives display activity against staphylococcal biofilms as well as internalized bacteria within osteoblast compared with other commonly used agents and, moreover, that rifampin can be loaded and eluted from PMMA beads successfully, despite previous literature suggesting otherwise [16,27]. These in vitro results indicate that for orthopaedic infections involving S. aureus biofilms, rifampin may be an applicable alternative to currently used agents in orthopaedic and trauma surgery.…”
Section: Discussionmentioning
confidence: 83%
“…Matos et al studied a new delivery system of levofloxacin by calcium phosphate particles, which were added to PMMA. However, the addition of rifampicin to PMMA prevented complete polymerization becoming unsuitable for use in clinical practice, despite the adequate in vitro release and good activity against S. aureus . The proposed mechanism is that rifampicin reacts with dibenzoyl peroxide (initiator) and/or dimethyl‐p‐toluidine (activator) being unable to react with the methylmethacrylate, and therefore the radical polymerization is inhibited…”
Section: Discussionmentioning
confidence: 99%
“…Han et al reported that rifampicin‐loaded bone cement could not be used to manufacture spacers because of its delayed polymerization. They studied the rifampicin elution from CMW®3 (Depuy, Warsaw, IN) discs cements in PBS on days 1, 3, 7, 14, and 30, using 1, 2, or 4 g rifampin per 40 g PMMA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation